Tail loss incidence in the Chihuahuan fringe toed-lizard Uma paraphygas (Squamata: Phrynosomatidae) - Gamaliel Castañeda; Cristina García-De la Peña; Héctor Gadsden; Armando J. Contreras-Balderas; William E. Cooper Jr. (Revista Mexicana de Biodiversidad)
We analyzed lizard population density and tail loss frequency in 2 populations of Uma paraphygas to determine if the proportion of lizards with tail loss was different between populations, sexes, and age classes. Also, we estimated unbroken and regenerated tail growth rates for adult males and females, and juveniles. Data were collected between fall 1997 and summer 1999. Tail loss incidence was relatively low overall, but was significantly higher at the site (Dune 1) with lower vegetation cover. Adult lizards showed a higher tail loss frequency than juveniles at the site with higher vegetation density (Dune 2); there was no difference between adult males and females in both dunes. Observations on 33 lizards with bite marks suggest that intraspecific encounters are not a direct cause of caudal autotomy in this species. The caudal growth rates of lizards were similar for unbroken and regenerated tails between sexes and among age classes.